2016
DOI: 10.2174/1874844901603010215
|View full text |Cite
|
Sign up to set email alerts
|

Water Soluble Chitosan Mediated Voriconazole Microemulsion as Sustained Carrier for Ophthalmic Application: In vitro/Ex vivo/In vivo Evaluations

Abstract: Background: Voriconazole (VCZ) is a lipophilic candidate, effective against fungal infections like ocular keratitis and endopthalmitis. Objective: The purpose to develop, optimize and characterize voriconazole microemulsion as sustained medication for ophthalmic application. Methods: The pseudo-ternary phase diagrams were developed using oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Bhosale et al found a higher VCZ corneal permeation with microemulsion containing IPM but their T max was observed at 4 h. This was ascribed to the synergy of the bioadhesive effect and the polycationic nature of the modified chitosan solution in their microemulsion formulation. [ 11 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhosale et al found a higher VCZ corneal permeation with microemulsion containing IPM but their T max was observed at 4 h. This was ascribed to the synergy of the bioadhesive effect and the polycationic nature of the modified chitosan solution in their microemulsion formulation. [ 11 ]…”
Section: Resultsmentioning
confidence: 99%
“…This is not the case with conventional SNEDDS, which are diluted after contact with tear fluid as well as other nanoformulations such as microemulsions and solid lipid nanoparticles in which the amount of instilled surfactant is relatively high. [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…After the development of fungal infection, formulations (MCNNs) and marketed preparation (NTF (5% w/v)) were administered topically into the eye of rabbits. In each group that was infected with Candida albicans, the left eyes of rabbits served as control and were treated with sterile saline solution whereas MCNNs and NTF were administered to the right eyes (62). The eyes of each group were examined on days 0, 7, 14, and 21 for the status of healing, corner vascularization, iritis, hypopyon, and macular nebula.…”
Section: Ulcer Healing Activitymentioning
confidence: 99%
“…Finally, in vivo studies on rabbit eyes demonstrated that voriconazole was detected in aqueous humor and the corneal bioavailability was improved significantly. 84 Da Silveira et al aimed to develop amphotericin B-loaded ocular MEs by titration method. The toxicity of the MEs was assessed by in vitro toxicity assay against red blood cells and it was found relatively low.…”
Section: Novel Ocular Microemulsionsmentioning
confidence: 99%